Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae): reclassification of eight species to Antitrogus Burmeister, 1855 and Barryfilius new genus - Allsopp, Peter G. (Zootaxa, 2022)
The status and generic placement of nine species of Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae) are reassessed. The monotypic genus Othnonius Olliff, 1890, is synonymised with Antitrogus Burmeister, 1855 (new synonym), resulting in Antitrogus batesii (Olliff, 1890) new combination. Lepidiota ciliata Britton, 1978 is transferred to Antitrogus as Antitrogus ciliatus (Britton) new combination. A group of six species attributed to Lepidiota Kirby, 1828 that do not have the scales characteristic of that genus are transferred to Barryfilius new genus as Barryfilius laevis (Arrow, 1932) new combination (type species), Barryfilius centralis (Britton, 1978) new combination, Barryfilius contiguus (Britton, 1978) new combination, Barryfilius lewisae (Britton, 1978) new combination, Barryfilius quinarius (Britton, 1978) new combination, and Barryfilius vernus (Britton, 1978) new combination. Lepidiota oblonga Brenske, 1900, is shown to be a junior synonym of Lepidiota rothei Blackburn, 1888 (new synonym). Revised keys to the genera of Australian Melolonthini, and to the species of Antitrogus and Australian Lepidiota are provided. The higher classification of the group is reviewed, and a checklist of Australian genera and species is given.